Upaya Penanggulangan Hipertensi Pada Lansia Melalui Pemberian Terapi Herbal : Seduhan Bawang Putih Dan Bunga Rosella - Sugiarti Sugiarti; Rachel Dwi Wilujeng; Ayuni Fethi Releghea (Pelita Medika, 2021)
Background: Elderly is a condition characterized by a person's failure to maintain balance against physiological stress conditions. This failure is related to a decrease in the ability to live and an increase in individual sensitivity. The incidence of hypertension in the elderly tends to equal even higher than that of men because of the decreased protective effect of the hormone estrogen. And people who are more than 45 years are a risk factor for hypertension. Based on a preliminary study conducted in the working area of ​​the Dukuh Kupang Puskesmas in Surabaya in January and February 2016, the target number of elderly people is 2,244, and 70 people with hypertension. One of the non-pharmacological treatments in dealing with hypertension is herbal therapy, including steeping rosella flowers (Hibiscus sabdariffa linn) and garlic (Allium sativum L) which are based on research trials proven to have the same effectiveness in treating hypertension. The purpose of this community service is to overcome the incidence of hypertension in the elderly through the provision of herbal therapy in the form of steeping rosella flowers and garlic. The target population for this community service is the elderly and elderly cadres in the Elderly Posyandu in the working area of ​​Puskesmas Dukuh Kupang, Surabaya. Method : The method of implementation in this activity is the empowerment of the elderly and elderly cadres through routine tension checks and training to make steeping garlic and rosella flowers which can be given to elderly suffering from hypertension. Result: The result of this activity is that the elderly and cadres play an active role in the manufacture and consumption of this brew. It is hoped that hypertensive elderly people will experience a decrease in blood pressure. Conclusion: Based on this, it can be concluded that the efforts to provide herbal therapy: garlic and rosella flowers are effective in overcoming hypertension in the elderly.